2015
DOI: 10.1097/jom.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Work and Health Among Latina Mothers in Farmworker Families

Abstract: Background Work organization is important for the health of vulnerable workers, particularly women. This analysis describes work organization for Latinas in farmworker families and delineates the associations of work organization with health indicators. Methods 220 Latino women in farmworker families completed interviews from October 2012 - July 2013. Interviews addressed job structure, job demand, job control, and job support. Health measures included stress, depressive symptoms, physical activity, family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
(72 reference statements)
4
23
1
Order By: Relevance
“…Employed Latinas, whether farmworkers or working in other manual occupations, have higher average stress and anxiety scores than do unemployed Latinas. Stress among the Latina farmworkers and employed non-farmworkers is similar to that reported for women in farmworker families, one-third of who were not employed (Arcury et al 2015a). Stress among these employed women is considerably greater than that reported among male Latino farmworkers with H2-A visas (Arcury et al, 2015b).…”
Section: Discussionsupporting
confidence: 71%
“…Employed Latinas, whether farmworkers or working in other manual occupations, have higher average stress and anxiety scores than do unemployed Latinas. Stress among the Latina farmworkers and employed non-farmworkers is similar to that reported for women in farmworker families, one-third of who were not employed (Arcury et al 2015a). Stress among these employed women is considerably greater than that reported among male Latino farmworkers with H2-A visas (Arcury et al, 2015b).…”
Section: Discussionsupporting
confidence: 71%
“…In fact agricultural workers experience heat-related deaths at an annual rate that is 20 times that of the U.S. civilian workforce (2). Beyond experiencing adverse environmental conditions at their workplace, agricultural workers experience a high level of vulnerability due to socioeconomic disparities including decreased access to healthcare, separation from their families, low income, crowded housing often in poor condition, and little control over their work environments (3)(4)(5)(6)(7). While the threats of HRI in this population are well-recognized there have been few studies that actually capture the heat conditions of the worksite, nor have researchers assessed the validity to which environmental monitoring station reflect the temperatures at the worksite.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike earlier studies, 7 most mothers reported having had interpreters or providers who spoke their language. Parents struggle to take children to well-child care when many (61%) of these mothers work, but do not have paid sick leave (6.8%) or health insurance (7.6%); 28 few have spouses with paid sick leave or health insurance. 1 …”
Section: Discussionmentioning
confidence: 99%